Improving practice through audit: administration of blood transfusions within a hospice setting. Issue 2 (1st September 2011) - Waddell, Jennifer; Hodgson, Aruna; Wiseman, Jenny
Abstract : Background: The cause of anaemia in palliative care patients is often multifactorial. Symptom burden is important when deciding whether to transfuse or not. Although formal consent for transfusion of blood products is not legally required, it is good clinical practice to inform the patient of potential risks and benefits. Following the Safer Practice Notice 14 "Right patient, right blood" in November 2006, national competencies for clinical staff involved in blood transfusions were introduced. The hospice decided to look at the blood transfusion process. Aims: To assess whether aspects of the blood transfusion process were adequately documented, including consent, provision of patient information leaflets, symptomatic benefit following blood transfusion and decisions regarding the appropriateness of future blood transfusions. Methods: Retrospective audit of patients receiving a blood transfusion within the inpatient unit or day hospice, against hospice standards. Data collected included demographics, haemoglobin (Hb) and symptoms pre-transfusion, blood prescription details, documentation of consent and decisions about whether future transfusions would be appropriate. Initial data collection period June to November 2007. A blood transfusion proforma was developed and introduced. Repeat data collection period April to September 2010. Results: A comparable number of blood transfusions were given in each period. Documentation of informed consent improved from 4% to 81% transfusions. Use of information leaflets increased from 0% to 29% transfusions. The number of transfusions that symptoms were not documented was reduced from 62% to 10%. Fatigue was the most common symptom reported in each cycle. Documentation of decisions about whether future transfusions were appropriate improved from 17% to 24%. Conclusion: The proforma has improved the documentation of symptoms, consent and use of information leaflets. Further improvement is needed in other areas. This will be achieved through dissemination of audit results, adjustments to current proforma and staff education. A re-audit is planned for the future.